The Influence of Customer Experience, Product Quality, and Price Perception on Customer Satisfaction with Chocolate Ice Cream in Sidoarjo - Danu Utoyo Kurniawan; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the impact of customer experience, product quality, and price perception on customer satisfaction for chocolate ice cream in Sidoarjo. Data was collected through a questionnaire distributed to all buyers of chocolate ice cream from the Kuweentel outlet in Sidoarjo. The method used in this research is quantitative with a cross-sectional design, utilizing the Statistical Package for the Social Sciences (SPSS) to analyze statistical data by creating tabulations, charts, plots of various distributions, descriptive statistics, and complex statistical analyses.